(untitled) (Research, Society and Development, 2020)
The happy-tree (Polyscias spp.) is a shrub belonging to the family Araliaceae. The objective of this study was to evaluate the babaçu decomposition stem (CBD) as a substrate in the vegetative propagation of the tree of happiness. The experiment was carried out in a greenhouse with 75% light, from August to September 2018, at the Center of Agrarian and Environmental Sciences (CCAA) of the Federal University of Maranhão (UFMA). We adopted the completely randomized design with six treatments composed of CBD, in the following proportions: S1: 0%, 20%, 40%, 60%, 80%, and 100% CDB, plus soil, consisting of 4 replicates, and each replicate contained 3 units, totaling 12 experimental units per plot. The analyzed variables were: percentage of survival of the cuttings (PS); number of shoots (NB); leaf area (FA); length of largest shoot (CMB); diameter of the largest bud (DMB); root length (CR); root volume (VR); and root system (MSSR). There was a significant effect (p <0.01) for DMB and CR, and (p <0.05) for CMB and MSPA, however, there was no significant difference in NB, PS, AF, MSSR, and RV. The CBD can be used as a substrate in the vegetative propagation of tree of happiness.